Competition, loan rates and information dispersion in microcredit markets - Guillermo Baquero; Malika Hamadi; Andréas Heinen (European School of Management and Technology (ESMT), 2012)
We study the effects of competition on loan rates and portfolio-at-risk in microcredit markets using a new database from rating agencies, covering 379 microbanks located in 67 countries between 2002 and 2008. Our study reveals different competitive effects in nonprofit and for-profit microbanks. We find that for-profit microbanks charge significantly lower rates and exhibit improved portfolio-at-risk in less concentrated markets. In particular, the effect of concentration on loan rates is nearly three times the one reported in previous studies in banking. In contrast, nonprofit microbanks are relatively insensitive to changes in concentration. We control for interest rate ceilings, which very significantly reduce rates in for-profit microbanks. However, our study also uncovers a competitive interplay between for-profit and nonprofit microbanks. In particular, the PAR of nonprofit microbanks deteriorates when the proportion of profit-oriented microbanks increases. Finally, we find evidence consistent with dispersion of borrower-specific information among competing microbanks in the for-profit sector, even after controlling for the presence of credit registries.
urn:nbn:de:101:1-201206287190
Keywords: D4; G21; L1; O1; 650; bank competition; microfinance; microcredit; microbank; loan rates; information dispersion; PAR; portfolio quality; Mikrofinanzierung; Kreditgeschäft; Wettbewerb; Informationsverbreitung; Welt